PENGARUH VARIASI JUMLAH TELUR ITIK TERHADAP RESPON UJI ORGANOLEPTIK TILIAYA - Mexiko Kadir; Siswatiana Rahim Taha; Ellen J Saleh (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2019)
This study aims to determine the effect of variations in the number of duck eggs on organoleptik tiliaya test responses including, texture,color, aroma, taste and prence. The panelist used in this study housed twenty people with categories of untrained panelists with a score one fiver. The study design used in the study was a completely rando mized consisting of four treatments and four replications namely p one duack egg, p two five duck eggs, p three eight duck egs, p four eleven duck eggs then the data obtained were analyzed using Anova analysis of varias and if there were differences real continued with the the Duncan further test. The results of the study show that there were is an effect of appromimately five percent real diffences on all treataments. In this case the treatment of Aroma Tiliaya panelists gave the highest value in the treatment of p one with two duck eggs with an average value of three point eight. In the Tiliaya color with the treatment of p one with two duck eggs obtain the highest average of three poin nine four. Intreatment p one with two duck eggs where the Tiliaya taste gets an average value of three point nine five. I treatment p one with two duck eggs where Tiliaya texture has an average value of four point zero eight. In treatment p one with two duck eggs where the general prefence for Tiliaya obtained an average value of three point nine seven. So it can be concluded that the value of a processed food producti is very decisive for the panelis, especially in Aroma, Color, Taste, Texture, general preference, which can affect the characteristic of the Tiliaya.